Color stability of composites subjected to accelerated aging after curing using either a halogen or a light emitting diode source - Pires-de-Souza,Fernanda de Carvalho Panzeri (2007)
The purpose of this study was to evaluate, in vitro, the color stability of three composite resins of two different shades (A3 and C3) cured with either a quartz tungsten halogen (QTH) or a light emitting diode (LED) source. Forty specimens (20 x 2 mm) were prepared for each composite (Tetric Ceram®, Heliomolar® and Esthet-X®), being 20 for each shade. In each group, 10 specimens were light-cured using the QTH unit and 10 with the LED source. The shade of the materials was evaluated before and after submitting the specimens to artificial accelerated aging (4 h UV-B/4 h condensing vapor), using a reflection spectrophotometer. deltaE means were calculated and analyzed statistically by 2-way ANOVA and Tukey's test at 5% significance level. Both A3 and C3 shades of Esthet-X composite resin showed the lowest color change when cured with the QTH light, while Tetric C3 cured with the QTH light showed the highest color change.